Economical and Efficient Electrochemical Sensing of Folic Acid using a Platinum Electrode Modified with Hydrothermally Synthesized Pd and Ag Co-Doped SnO2 Nanoparticles. Issue 13 (1st January 2019) - Sharma, Asha; Arya, Sandeep
Abstract : In this work, an economical method of electrochemical sensing for the detection of Folic acid (FA) has been reported. A sol gel assisted hydrothermal technique was used to synthesize undoped, Ag doped and Pd-Ag co-doped, SnO2 nanoparticles. The structure, morphology, shape, and chemical composition of the synthesized nanoparticles were confirmed by XRD, FESEM, TEM, FTIR, and EDS spectroscopic techniques. Cyclic voltammetry (CV) and Differential pulse voltammetry (DPV) studies confirmed that Pd and Ag co-doped SnO2 nanoparticles show significant competency in sensing FA due to their high specific surface and excellent electrical conductivity. The platinum (Pt) electrode was modified with the synthesized nanoparticles to serve as a precise sensing agent. The resulting electrode showed viable sensing performance for detecting FA in a pharmaceutical sample with excellent recovery. The calibration plot is linear in the concentration range of 22 μM–112 μM and has a 3.47 μM detection limit. The assay is outstandingly reproducible, selective and stable.